Female Bodies and Sexuality in Iran and the Search for Defiance - Sharifi, Nafiseh (Springer International Publishing, 2018)
This book uses storytelling as an analytical tool for following wider social attitude changes towards sex and female sexuality in Iran. Women born in 1950s Iran grew up during the peak of secularization and modernization, whereas those born in the 1980s were raised under the much stricter rules of the Islamic Republic. Using extensive ethnographic research, the author juxtaposes narratives of body and sexuality shared by these different generations of women, showing the intricate ways in which women construct and convey meanings and communicate their emotions about the unspoken aspects of their lives. Nafiseh Sharifi is Postdoctoral Fellow at the Centre for Gender Studies at the School of Oriental and African Studies, University of London, UK. .